The Value of Character Education in The Ramatambak Puppet Story as a Medium for Learning The Character of Students - Suprapto, Yuni; Mulianingsih, Ferani; Astuti, Andarweni; M. Nur, Dany Miftah; Setiyoko, Didik Tri (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
This paper uses a literature study approach, by dissecting the story of the Wayang Rama Tambak which is analyzed using the theory of character education according to Lickona and Character Education. Lickona's theory is; 1) Love of kindness; 2) Affection; 3) Dare; 4) The value of hard work; 5) Honest; 6) Justice; 7) Value of Responsibility; 8) Cooperation Value. As for the theory of character education values according to Ki Hajar Dewantara, there are also seven that can be imitated from the Rama Tambak puppet story, along with the analysis; 1) Exercise of the Heart (Ethics); 2) Thought (Literacy; 3) Leadership; 4) Gotong Royong; 5) Trust; 6) Nationalists; 7) Character. Wayang is an original Indonesian heritage which contains various character education values that can be used as role models for students, especially elementary school children. This character habituation can be accustomed by imitating the characters or puppet figures.